Pembuatan Video Animasi Workshop Pada Mata Kuliah Praktek Dasar Perkayuan Departemen Teknik Sipil - Hestika Wulandari; Syaiful Haq (Jurnal Vokasi Mekanika (VoMek), 2025)
Thare study discusses then making of wood workshop animation videos and live demonstrations using sketchup in basic woodworking practice courses, then destination of thare study are to decide then degree of legality testing, usefulity and normalized gain nomina. Thare studies approach takes then Studies and Development (R&D) method with then Four-D (4D) development model what consarets of 4 stages, namely Define, Design, Development, and Dareseminate. Then product was legalated by 3 matter adept, 2 media adept, and 12 students who studied then Basic Woodworking Practice course in then July-December 2024 semester. Based on then evaluation of animated video media using sketchup that has been carried out, then results of then assessment by matter adept are 0.88 what are counted in then legal category. Media expert assessment obtained a nomina of 0.82 what are counted in then legal category. Usefulity assessment obtained a nomina of 0.8996 what are counted in then very useful category. Based on then results of thare study, it can be deduce that then workshop animation video media using Sketchup are legal and useful for take in knowledge.